PENAWARAN SAYUR KELOR (MORINGA OLEIFERA) MENTAH PADA PASAR TRADISIONAL AMBUAU INDAH DI PESISIR KECAMATAN LASALIMU SELATAN - Antasalam Ajo (Media Agribisnis, 2020)
The supply of moringa leaf vegetables in rural coastal areas has its own characteristics compared to the supply of commercial commodities in general. This happens because of the strong social relations in rural areas, and the form of products offered is raw products. The purpose of this study is to identify the factors that influence the number of raw moringa vegetable supply at the trader level and analyze the effect of each on the number of raw moringa vegetable supply. The research data were collected from the raw moringa vegetable traders in the Ambuau Indah Traditional Market in Lasalimu Selatan Sub-district as many as 21 respondents obtained for 3 months, from February to April 2020, then analyzed descriptively and using multiple regression with variables dummy. The results of the study are the factors identified as a consideration of traders determining the offer of moringa leaf vegetables are the purchase price (71%), sales costs (60%), profits (75%), vegetable origin (50%), but there are social reasons which help meet the needs of other people's vegetables (90%) and in order to make money (92). Meanwhile, the variable purchase price, cost of sales, profits, and vegetable origin simultaneously able to contribute effectively to predict the amount of appropriate vegetable deals determinant coefficient (R2) of 0.762, or Adjusted R Square of 0.682. However, the relationship between the purchase price and selling cost variables with the number of supply variables is negative, while the profit and vegetable origin variable is positive, each with a small value. Keywords: supply, rural coast, raw moringa vegetable